A Social Psychological Perspective on the Identity Repertory of Alevis in the Urban Life: The Role of Ethnic Identity, Mother Tongue, and In-Group Representations in the Self-Categorization (Journal of Alevism-Bektashism Studies, 2021)
Despite the increasing acceleration in academic studies on “Alevism”, social scientific studies on “Alevis”, as the holder of Alevism and the social subjects shaping Alevism, seem to be limited. It is aimed to study the identity definition and identity construction processes of Alevis within a “social psychological perspective”, as a solution-seeking against this limitation. In this study, the notion of “humanity”, which is considered as the belief-theosophy and socio-history related authenticity of Alevis/Alevism, took a valuable position as an example of collective identity construction. In the literature, it is evaluated that urbanization and modernization led Alevism to be a phenomenon experienced externally. Accordingly, to study of humanity notion and identity repertory of the Alevi subject in urban life in terms of “ethnic identity”, “mother tongue” and “social representations towards in-group” constitutes this research’s scope. The survey within the study was conducted in Istanbul and Izmir with 142 Alevi participants (Mage = 37.4 and 64 of them were women). The obtained data were analyzed by content analysis, descriptive analysis, kappa analysis, chi-square analysis, and one-way ANOVA. According to the findings, 9.6% of the identity statements/elements (f = 1136) that were declared by the participants consist of identity elements at the superordinate abstraction level of self-categorization that based on the usage of the collective identity category of humanity. In terms of statistical significance, the frequencies of humanity collective identity, group identity, and personal/relational identity among the participants are dependent on ethnic identity and mother tongue. Five categories revealed in social representations towards in-group: (1) Alevis with regards to Humanity Identity and Ethical Stances, (2) Alevis with regards to Socio-Cultural Capital and Features, (3) Social Status and Political Engagements of Alevis, (4) Traits of Alevis, (5) Alevis as Faith-based Cultural Group. The results showed that ethnic identity and mother tongue are the factors to be considered when studying the Alevi identity, and in-group representations can make important contributions to understand the content of the identity process. In the last part of the paper, the findings at issue were discussed in terms of social identity and social representations approaches according to social psychological standpoint, and with referring to related social science disciplines; in addition to this, the scope/limitations of the present study were assessed.